1973
DOI: 10.1346/ccmn.1973.0210516
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size-Shape Relationships in Georgia Sedimentary Kaolins—II

Abstract: Abstract---Crude sedimentary kaolin clay from central Georgia, U.S.A., which had a wide distribution of particle size, was divided into several size fractions by repeated sedimentation in water. The resulting fractions had approximately a 2 : 1 ratio in dia. between their upper and lower limits. Each fraction was then studied by transmission and scanning electron microscopy and characterized in terms of surface area (both geometric and by gas adsorption), particle shape and impurity analysis.Particle diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…After purification, clay fractions of different particle size were obtained by centrifugation in a Hitachi Himac CR20B2 refrigerated centrifuge, using the Stokes' law (37)(38)(39)(40)(41)(42)(43).…”
Section: Methodsmentioning
confidence: 99%
“…After purification, clay fractions of different particle size were obtained by centrifugation in a Hitachi Himac CR20B2 refrigerated centrifuge, using the Stokes' law (37)(38)(39)(40)(41)(42)(43).…”
Section: Methodsmentioning
confidence: 99%
“…The XRD profiles of 00l basal-plane reflections were selected for microstructural analysis due to the morphological importance of these planes in terms of the shape (Olivier and Sennett, 1973) and due to their relatively high intensity and the lack of overlapped neighboring peaks.…”
Section: X-ray Diffraction Microstructural Analysismentioning
confidence: 99%
“…The structural order or disorder of kaolinite grains has been studied, usually by powder X-ray diffraction (XRD) methods, in order to correlate such data with geological environment, mechanical processing (such as grinding or transport), or industrial utility (Murray and Lyons, 1956;Brindley et al, 1986). In addition, studies that assess the variation of a kaolinite property with particle size have noted widely varying correlations between, for example, particle size and "crystallinity index" for a given kaolinite sample (Olivier and Sennett, 1973;Brindley et al, 1986;Tettenhorst and Corbato, 1986;Lombardi et al, 1987), Some of this particle size variation observed in natural samples may be due to inappropriate use of sizing techniques for a particular size range (e.g., McCave et al, 1986), poor reproducibility of the sizing technique; or, alternatively, this may be due to natural variations in kaolin size distributions with a specific property. For some clays, the <2 pm size range is an important fraction that may determine the nature of bulk physical properties.…”
Section: Introductionmentioning
confidence: 99%